Identification of alternative hosts of the tomato leafminer Tuta absoluta (Meyrick, 1917) (Lepidoptera: Gelechiidae) in West Africa - Sawadogo, Mathieu Wendnéyidé; Ahissou, Regis Besmer; Somda, Irénée; Nacro, Souleymane; Legrève, Anne; Verheggen, François (African Entomology, 2022)
Tuta absoluta (Meyrick, 1917) (Lepidoptera: Gelechiidae) reached West Africa in 2012 and has since become a major tomato pest. Various alternative strategies for pest control have been identified worldwide, including crop rotation, to deprive the insect of its food. However, this method can only be implemented if a good knowledge of the local host plants of the leafminer have been identified. Here, we have assessed the capacity of Tuta absoluta to develop on 27 common vegetable crops in West Africa, representing the Poaceae, Apiaceae, Convolvulaceae, Amaranthaceae, Malvaceae, Lamiaceae, Cucurbitaceae, Fabaceae, Brassicaceae, Asteraceae, Solanaceae, and Amaryllidaceae. The tomato leafminer was only able to develop and complete its life cycle on crops within the genus Solanum. Among the 27 plant species tested, Solanum lycopersicum L. (tomato) was identified as the best host, allowing for rapid development (22.2 ± 1.4 days) and a high survival rate (84%). Solanum tuberosum L. (Irish potato) (24.4 ± 0.8 days; survival rate 40%), Solanum aethiopicum L. (African eggplant) (24.3 ± 0.6 days; survival rate 52%) and Solanum melongena L. (eggplant) (25.9 ± 1.8 days; survival rate 24%) were three other possible hosts. Larval development occurred on onion (Allium cepa L.), but not pupation. A strategy that includes a prolonged absence of the genus Solanum in a production area would be associated with a considerable reduction in leafminer population size.